Principal Component Analysis of the Running Ground Reaction Forces With Different Speeds - Yu, Lin; Mei, Qichang; Xiang, Liangliang; Liu, Wei; Mohamad, Nur Ikhwan; István, Bíró; Fernandez, Justin; Gu, Yaodong (Frontiers in Bioengineering and Biotechnology, 2021)
Ground reaction force (GRF) is a key metrics in biomechanical research, including parameters of loading rate (LR), 1st impact peak, 2nd impact peak, and transient between 1st and 2nd impact peaks in heel strike runners. The GRFs vary over time during stance. This study was aimed to investigate the variances of GRFs in rearfoot striking runners across incremental speeds. Thirty female and male runners joint the running tests on the instrumented treadmill with speeds of 2.7m/s, 3.0m/s, 3.3m/s and 3.7m/s. The discrete parameters of vertical average loading rate (VALR) in the current study are consistent with findings from the literature. Principal component analysis was modelled to investigate the main variances (95%) in the GRFs over stance. The females varied in the magnitude of braking and propulsive forces (PC1, 84.93%), while the male runners varied in the timing of propulsion (PC1, 53.38%). The female runners dominantly varied in the transient between the 1st and 2nd peaks of vertical GRF (PC1, 36.52%) and LR (PC2, 33.76%), while the males variated in the LR and 2nd peak of vertical GRF (PC1, 78.69%). Knowledge reported in the current study suggested the difference of the magnitude and patterns of GRF between male and female runners across different speeds. Knowledge reported in the current study may have implications for the prevention of gender-specific running-related injuries and could be integrated with wearable signals for the in-field prediction and estimation of impact loadings and ground reaction forces.